Prospek dan Kendala Pengembangan Usaha Ternak Domba di Kecamatan Cilongok, Banyumas - Hernanto, Angga; Muatip, Krismiwati; Haryoko, Imbang (ANGON: Journal of Animal Science and Technology, 2020)
Background. This study aims to determine the prospects and constraints of the development of sheep business and examine efforts to develop sheep farms in the District of Cilongok. Materials and methods. The number of research samples were 56 respondents. The target of the research is the breeder and sheep breeding business in Cilongok District, Banyumas Regency. The method used is a survey method for farmers in Cilongok District, namely by interviewing farmers. Sampling of the area is done intentionally (Purposive Sampling). Results. Research results obtained thatsheep business prospects in the Cilongok area are quite good with the support of productive breeders age, vast land, abundant agricultural waste, facilities and infrastructure available so that farmers can remain optimistic that market opportunities will increase. Thus, the sheep business has a better future. The constraints of the sheep business in the Cilongok area are sideline business, adequate Human Resources (HR), traditional maintenance, low breeders' education, lack of technological understanding, marketing is still conventional, institutions are less active and extension workers rarely provide socialization. Conclusion. Strategies that can be carried out in the development of sheep business in the District of Cilongok are by increasing maintenance facilities by utilizing land availability, increasing performance to increase livestock population, optimizing livestock productivity to meet market demand and applying forage processing technology so that it becomes high-quality feed.